PRAWA PRACOWNICZE KOBIET W NORMACH MIĘDZYNARODOWEJ ORGANIZACJI PRACY I WSPÓLNOTY EUROPEJSKIEJ - Buchowska, Natalia (Wydział Prawa i Administracji UAM, 1999)
The Author has divided the existing legal regulations of the above mentioned institutions in three categories, and more particularly: - legal acts of protective nature, corrective legal acts, and - anti-discriminatory acts. Then the Author is occupied with some concrete provisions on elimination o f discrimination, provisions to guarantee equal salaries and protection o f women’s labour. According to the Author’s opinion the regulations bom within the ILO system are sufficient to guarantee a protection of work and an observation of women’s rights in work relations and as well they are also sufficient to secure equality o f rights of women and men. The norms adopted within the law of European Communi ties are in full conformity with standards elaborated by the ILO and in certain cases they are even superior.
WOMEN EMPLOYEE’S RIGHTS AS REGULATED WITHIN THE NORMS OF THE INTERNATIONAL LABOUR ORGANIZATION AND EUROPEAN COMMUNITIES